Removal of Harmful Dyes Using Some Algae - Zariç, Özgür Eren; Yeşildağ, İrem; Yaygır, Sidar; Çelekli, Abuzer (3rd International Congress on Plant Biology, 2022)
Algae are defined as a group of predominantly aquatic, photosynthetic, and nucleus-bearing organisms that lack the true roots, stems, leaves, and specialised multicellular reproductive structures of plants. Algae have different applications, the most important of which is biological treatment. It is known that the harmful dyes released because of industrial production cause damage to the environment. In this review, information is given on the removal of undesired dyes by using some (Chara contraria A.Braun ex Kützing, Cladophora glomerata (L.) Kuetzing, Tetradesmus obliquus (Turpin) M.J.Wynne). Google Scholar, Scopus, SpringerLink, Web of Science, and Mendeley databases were searched to obtain appropriate publications to support the goal of this study, using “Chara contraria”, “Cladophora glomerata”, “Tetradesmus obliquus”, “Harmful Dyes”, “Biological treatment” and combinations of them. Due to the high tolerance value of these algae against harmful dyes, it has been determined that they are used in the removal of harmful dyes. In line with the results; It was determined that it was used in the removal of Lanaset Red G by Chara contraria, textile cotton dyes by Cladophora glomerata and methyl red by Tetradesmus obliquus. Results indicate that these algae show a broad tolerance to hazardous dyes. The importance of algae for biological treatment and its economy has been determined.